An evaluation of local, national and international perceptions of benefits and threats to nature in Tierra del Fuego National Park (Patagonia, Argentina). (15th August 2019) - Mrotek, Aaron; Anderson, Christopher B; Valenzuela, Alejandro EJ; Manak, Leah; Weber, Alana; Van Aert, Peter; Malizia, Mariano; Nielsen, Erik A
Summary: Environmental scientists and managers increasingly recognize that socio-cultural evaluations expand the understanding of human–nature relationships. Here, user groups' perceptions of the benefits from and threats to nature were analysed in Tierra del Fuego National Park, Argentina. We hypothesized that the different relationships of users to this place would lead to significantly different valuations among local Ushuaia residents (n = 122), Argentine nationals (n = 147) and international tourists (n = 294). All users perceived a broad spectrum of benefits. The three groups assessed intrinsic and relational values more highly than instrumental benefits, and significant differences included a higher mean valuation of benefits by Argentine visitors. Overall, threats were less perceived than benefits, and significant differences included a higher mean threat assessment by Ushuaia residents. To explain these relationships, we found that mean valuations of benefits and threats were weakly related to increased biodiversity knowledge for residents and international tourists, but not for Argentine visitors. These findings can orient environmental management in Patagonia and elsewhere by identifying areas where information can improve user experiences and by contributing a more pluralistic understanding of nature from multiple stakeholders.